An analysis of Ecological Crisis in Contemporary in Literature in Earth Day by Jane Hyatt Yolen - P. Kavitha, (International Journal of Scientific Research in Science and Technology, 2024)
This paper explores the Ecological Crisis in Contemporary Literature. frequently when changes occurs to the environment. It’s continued survival ecological crisis are include environmental damage, air pollution, water pollution, earth pollution. This is referred in the Earth Day by Jane Hyatt Yolen. She is an American writer, focus on weaving folklore, fantasy, and historical events into stories for children and young adults. The ecological crisis is the same in the big developed country as it is in the small undeveloped country. The main theme of Earth Day Protect the earth and Respect the earth.
Keywords: Protect the earth; free from pollution; save trees